Efektivitas Pelatihan “Let’s Learn to Pause & Breathe” untuk Menurunkan Kesulitan dalam Meregulasi Emosi pada Siswa Kelas XII SMA X Gresik - Elizabeth Findriany Tionardi; Ika Famila Sari (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
This training is intended to help increase students 'mindfulness so that it can help reduce students difficulties in regulating emotions. The aspect of mindfulness used in this training is based on aspects of the five facet mindfulness questionnaire (FFMQ) (Baer et al., 2006), namely nonreactivity to inner experience, observing, acting with awareness, describing/ labeling, and nonjudging of experience. Measurement of students' level of difficulty in regulating emotions using aspects of difficulties in emotion regulation (Roemer Gratz, 2004), namely nonacceptance of emotional responses, difficulties engaging in goals-directed behavior, impulse control difficulties, lack of emotional awareness, limited access to emotion regulation strategies and lack of emotional clarity. The results of the training show that the mindfulness training can help reduce the level of difficulty regulating emotions experienced by students (significance value is less than 0.05).